Efektivitas Pelatihan Kepemimpinan Bagi Staff pada Tadika Al Fikh Orchard HQ Malaysia - Al Hilal Hamdi Mnl; Isra Hayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effectiveness of leadership training for staff at Tadika Al Fikh Orchard HQ Malaysia. The research method used is qualitative with data collection techniques through interviews, observation, and documentation. The results of the study indicate that leadership training has proven effectively in improving the quality of human resources at Tadika. Staff become more confident in making decisions, are able to communicate effectively, and demonstrate a better work ethic. Challenges faced include time constraints, differences in participant backgrounds, and consistency in implementing training results in the field, so that appropriate strategies are needed to optimize the benefits of the training.